Apparatus at U.S. Department of Agriculture facility (1950)
General view of an unidentified apparatus, possibly a hopper or type of granulation equipment, at an unidentified U.S. Department of Agriculture facility, likely the U.S.D.A.'s Agricultural Engineering Laboratory. Three specimen jars, likely containing fertilizer and/or soil samples, are visible beneath the apparatus.
Keywords: Nitrogen fertilizer industry; Scientific apparatus and instruments; United States. Department of Agriculture; United States. Bureau of Chemistry and Soils; Machinery